From school improvement to sustained capacity : the parallel leadership pathway - Crowther, Frank, 1942- (Thousand Oaks, California : Corwin Press, 2011)
'Bestselling author Frank Crowther makes a compelling case for capacity building and parallel leadership as the keys to ensuring sustainable improvement. Research-based with tools and examples'-- Provided by publisher.
'In this sequel to Developing Teacher Leaders, bestselling author Frank Crowther builds on the key concept of parallel leadership to demonstrate its utility as a strategic managerial tool in building school capacity. From School Improvement to Sustained Capacity: The Parallel Leadership Pathway specifically demonstrates how district and school leaders can utilize parallel leadership to facilitate a sequential school capacity building process that will ensure school improvement and increased student success. Based on a recent research study which examined how principals and teacher leaders worked together over a 2-4 year period to develop and sustain enhanced quality in their workplaces, this book expands the definition of parallel leadership, refines the notion of teacher leadership and incorporates roles for middle managers and student leaders. Crowther's research evidence and cases from numerous school-based studies illustrate how these parallel leadership roles can be used to attain what he terms the six basic dynamics essential to any successful school capacity building and preservation effort'--
Includes bibliographical references and index.
Keywords: School improvement programs -- United States; School management teams -- United States; Educational leadership -- United States